Marine Cretaceous organic-walled dinoflagellate cysts from the Austral-Magallanes Basin. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Cretaceous marine sedimentary rocks from the Austral-Magallanes Basin have provided a valuable organic-walled dinoflagellate cyst record as a useful tool for biostratigraphical interpretations and paleo-oceanographical reconstructions. This paper contains a revision of the main dinoflagellate cyst information previously published in southwest Patagonia and the Continental Platform, encompassing two time intervals, the Late Hauterivian to Early Cenomanian and the Campanian to Maastrichtian. We present for the first time a sequence of Cretaceous diagnostic dinoflagellate cyst events identified at surface and subsurface sections throughout the Austral-Magallanes Basin. In ascending order, nineteen primary bioevents of first occurrence (FO), last occurrence (LO) and acme were recognized. Eleven biovents were identified in the Early Cretaceous: LO of Senoniasphaera tabulata, LO of Kleithriaphaeridium fasciatum, FO of Prolixosphaeridium parvispinum, LO of Phoberocysta neocomica, FO of Herendeenia postprojecta, FO of Odontochitina operculata, LO of Cassiculosphaeridia magna and the LO of Kaiwaradinium scrutillinum, Ovoidinium sp. Acme, LO of Dingodinium cerviculum and LO of Muderongia tetracantha. Nine bioevents were identified in the Late Cretaceous: FO of Odontochitina porifera, FO of Palaeohystrichophora infusorioides, FO of Nelsoniella aceras, FO of Nelsoniella tuberculata, FO of Xenikoon australis, LO Nelsoniella aceras, LO of Odontochitina spinosa, FO of Manumiella druggii and FO of Eisenackia circumtabulata. In general, the Austral-Magallanes Basin assemblages compare well with those coeval from the middle to high Southern Hemisphere latitudes sites, suggesting paleo-oceanographical connections between the southernmost tip of South America, Antarctica, New Zealand and Australia during the Cretaceous.